2007
DOI: 10.1016/s1872-2423(07)01003-4
|View full text |Cite
|
Sign up to set email alerts
|

Soluble guanylyl cyclases in invertebrates: Targets for NO and O2

Abstract: Soluble guanylyl cyclase (sGC) is probably the most prevalent target for NO in almost all species and tissues (Lucas et al., 2000). The native enzyme is usually a heterodimer (see below for exceptions to this) containing a single heme group (Lucas et al., 2000). In mammals, four subunits have been identified: α1, α2, β1 and β2. The major functional enzyme is the α1/β1 heterodimer (Lucas et al., 2000). The α2 is very similar in sequence to the α1 subunit and the α2/β1 heterodimer has similar properties to the α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Transient expression of different combinations of the Drosophila atypical sGCs in COS-7 cells showed that Gyc-89Da and Gyc-89Db form obligate heterodimers with Gyc-88E, and are potently activated in the absence of O 2 , therefore suggesting a function as O 2 sensors (Morton 2004b;Vermehren et al 2006;Morton and Vermehren 2007). Gyc-88E is also active as a homodimer (Morton 2004b;Huang et al 2007), directly binds O 2 and is also activated by reduced O 2 (Huang et al 2007).…”
mentioning
confidence: 99%
“…Transient expression of different combinations of the Drosophila atypical sGCs in COS-7 cells showed that Gyc-89Da and Gyc-89Db form obligate heterodimers with Gyc-88E, and are potently activated in the absence of O 2 , therefore suggesting a function as O 2 sensors (Morton 2004b;Vermehren et al 2006;Morton and Vermehren 2007). Gyc-88E is also active as a homodimer (Morton 2004b;Huang et al 2007), directly binds O 2 and is also activated by reduced O 2 (Huang et al 2007).…”
mentioning
confidence: 99%
“…Previous studies have shown that Gyc88E is active in the absence of additional subunits, while Gyc89Da and Gyc89Db enhanced the activity of Gyc88E when co-expressed, suggesting that these enzymes acted likely as heterodimers (Morton and Vermehren 2007;Morton 2011). It is important to mention that Gyc89Db is expressed in the brain during larval development (Langlais et al 2004)and produces cyclic GMP in response to low oxygen in vitro (Morton 2004;Vermehren et al 2006).…”
Section: Descriptionmentioning
confidence: 96%
“…7 The expression patterns of the Drosophila atypical sGCs showed that in larvae they are almost exclusively expressed in sensory and central neurons 14,15,18 and this distribution together with their biochemical properties suggested that they were ideal candidates for the O 2 sensors mediating behavioral responses to hypoxia. 19,20 Drosophila larvae respond rapidly to hypoxia by leaving their normal feeding positions (partially buried in their food) and initiating exploratory behaviors. 21 By inactivating the neurons that express Gyc-89Da with tetanus toxin (TTxN) we showed that these neurons were required for this behavioral response 19 but our initial efforts at establishing a role for the atypical sGCs in responses to hypoxia were hampered by the apparent redundancy between Gyc89Da and Gyc-89Db.…”
mentioning
confidence: 99%